High-thickness aluminum foil anode foil composite pulse waveform hole-making technology

By using composite pulse waveform hole generation process of high-thick aluminum foil anode foil, combined with the alternating use of low-frequency and high-frequency pulses, the problem of current enrichment during the hole generation process is solved, and the electrostatic capacity and mechanical strength of the corroded foil are significantly improved.

CN119361327BActive Publication Date: 2025-03-25NANTONG HAIXING ELECTRONICS +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411960101.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-25
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The high-thick aluminum foil anode foil has a large instantaneous current at the top during pulse waveform generation, resulting in enrichment of current at the sides of the electrode, causing the uniformity of the residual core to decrease and the penetration of the residual core to increase, thereby affecting capacity and mechanical strength.

Method used

The composite pulse waveform hole generation technology is adopted, and the alternation of high-frequency pulse superposition is performed in the middle and post-stage stage of tunnel hole growth, to optimize the current distribution and enrichment situation and prevent local current enrichment.

Benefits of technology

The hole density and uniformity of the surface of the aluminum foil are significantly improved, and the electrostatic capacity and mechanical strength of the corroded foil are thus improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361327B_ABST
    Figure CN119361327B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of pulse pore-forming technology of anode foil, and in particular to a composite pulse waveform pore-forming technology of anode foil of high thickness aluminum foil. The composite pulse waveform pore-forming technology of anode foil of high thickness aluminum foil of the present invention uses a low-frequency pulse in the initial stage of pore-forming, uses a high-frequency pulse in the middle and late stages of tunnel hole growth, and performs a low-frequency pulse again after alternating the low-frequency and high-frequency pulses for several times, thereby optimizing the structure and performance of the anodic oxide film, refining the pores, and improving the density and uniformity of the pores, so that the specific volume and mechanical properties of the finished corrosion foil are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pulse hole making in anode foil, and in particular to a composite pulse waveform hole making technology for anode foil with high thickness aluminum foil. Background Art

[0002] In the modern electronics industry, high-purity aluminum foil anode foil is an important component of electrolytic capacitors, and the optimization of its manufacturing process is crucial to improving the performance of capacitors. At present, many front-end companies use a single pulse waveform for hole-making in most of their production. Compared with the traditional DC hole-making anode foil, this hole-making method has a significant improvement in capacity. However, there is a large instantaneous current at the top during the pulse waveform hole-making process, and some hole-making waveforms cause the current to be enriched on both sides of the electrode, resulting in a decrease in the uniformity of the residual core and an increase in residual core penetration, thereby affecting the capacity and mechanical strength. In addition, high-thickness aluminum foil anode foil is particularly affected.

[0003] Patent document CN104505260A discloses a method for preparing medium and high voltage corrosion foil by pulsed DC superposition current. The invention generates holes by pulsed DC superposition current through a primary hole generation method. The process is simple, which improves the electrostatic specific capacitance and mechanical properties of the corrosion foil and solves the limitation that the power cannot be turned off during the hole generation process in the traditional corrosion process. However, the distribution uniformity of the holes on the surface of the aluminum foil obtained by the invention is still lacking, resulting in inconsistency in the specific surface area, which in turn affects the performance of the aluminum foil.

[0004] The composite pulse (pulse waveform superimposed pulse waveform) pore-forming technology, due to the superposition of pulse waveforms, allows the current to flow continuously, without instantaneous start current, thus reducing the instantaneous current at the top. At the same time, the composite pulse can make full use of the electromigration effect to optimize the distribution and enrichment of the current by reasonably designing the parameters of the pulse current, preventing excessive corrosion caused by local current enrichment, and making the distribution of the holes more uniform and the specific surface area higher. However, when the pulse is in operation, the frequency will also affect the morphology and distribution of the pores of the anode foil. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a composite pulse waveform pore-forming technology for high-thickness aluminum foil anode foil, so as to provide a pulse pore-forming technology for high-thickness aluminum foil anode foil, so that the high-thickness aluminum foil anode foil after pulse treatment has excellent electrostatic capacitance and mechanical properties.

[0006] Based on the above purpose, the present invention provides a high-thickness aluminum foil anode foil composite pulse waveform hole-making technology, comprising the following steps:

[0007] S1: Place the plain foil in a phosphoric acid solution and then take it out for washing;

[0008] S2: subjecting the aluminum foil obtained in S1 to a pore-forming treatment;

[0009] S3: performing hole expansion treatment on the aluminum foil obtained in S2;

[0010] S4: washing the aluminum foil obtained in S3 in a dilute hydrochloric acid solution, then washing it in a dilute nitric acid solution, and finally rinsing it with pure water and drying it;

[0011] S5: performing chemical treatment on the aluminum foil obtained in S4 to obtain a finished corrosion foil;

[0012] The pore forming treatment in step S2 is to place the aluminum foil obtained in step S1 in a mixed bath solution of 0.5-1 mol / L hydrochloric acid, 3.2-3.8 mol / L sulfuric acid and 0.01-0.05 mol / L phosphoric acid, and perform a composite pulse superposition pore forming treatment at a temperature of 60-73°C. The specific process is as follows:

[0013] First, 1.7-1.9 A / cm 2 Duration 0.5-2s, superimposed pulse, frequency 500-700Hz, duty cycle 30%-37%, superimposed size ±0.03-0.05A / cm 2 ; then at 1.2-1.7 A / cm 2 Duration 1.5-3s, superimposed pulse, frequency 700-800Hz, duty cycle 45%-50%, superimposed size ±0.03-0.05A / cm 2 ; then 0.5-1.2 A / cm 2 Duration 1.5-3s, superimposed pulse, frequency 700-800Hz, duty cycle 45%-50%, superimposed size ±0.03-0.05A / cm 2 ; then at 0.3-0.5 A / cm 2 Lasts 2-5s, superimposed pulse, frequency 800-900Hz, duty cycle 45%-50%, superimposed size ±0.02-0.03A / cm 2 ; Finally, 0.15-0.3A / cm 2 Duration 10-15s, superimposed pulse, frequency 1000-1500Hz, duty cycle 45%-50%, superimposed size ±0.01-0.015A / cm 2 After repeating the above pore-forming steps 3-5 times, 2 Duration 0.5-2s, superimposed pulse, frequency 500-700Hz, duty cycle 30%-37%, superimposed size ±0.03-0.05A / cm 2 .

[0014] Preferably, the concentration of the phosphoric acid solution in step S1 is 1.5-3 mol / L, the temperature is 65-70° C., and the time is 30-120 s.

[0015] Preferably, the smooth foil in step S1 is a smooth foil with a thickness of 140-150 μm.

[0016] Preferably, the pore expansion treatment in step S3 is to place the aluminum foil obtained in S2 in a mixed bath solution of 1.1-1.5 mol / L nitric acid, 0.05-0.1 mol / L phosphoric acid and 0.02-0.08 g / L sodium polystyrene sulfonate for pore expansion treatment.

[0017] Preferably, the temperature of the pore expansion treatment is 60-80°C and the constant current density is 0.12-17 A / cm 2 , duration is 13-16 minutes.

[0018] Preferably, in step S4, the concentration of the dilute hydrochloric acid solution is 0.03-0.1 mol / L, and the concentration of the dilute nitric acid solution is 0.1-0.2 mol / L.

[0019] Preferably, the washing temperature in the dilute hydrochloric acid solution in step S4 is 60-65° C., and the washing time is 1-3 min.

[0020] Preferably, in step S4, the washing in the dilute nitric acid solution is performed at a temperature of 65-70° C. and a washing time of 1-3 min.

[0021] Preferably, the pure water rinsing time in step S4 is 8-15 minutes.

[0022] Preferably, the drying temperature in step S4 is 180-270°C.

[0023] Preferably, the chemical formation process in step S5 is as follows: the obtained aluminum foil is placed in 90-95°C pure water and boiled for 7-15 minutes, then placed in a mixture of adipic acid (0.05wt%-0.2wt%), ammonium adipate (0.1wt%-0.3wt%), boric acid (0.1wt%-0.15wt%) and maleic acid (0.01wt%-0.1wt%) for primary chemical formation at 90-95°C for 7-10 minutes, with a chemical formation voltage of 160-170V, then placed in citric acid (0.04wt%-0.06wt%), ammonium citrate (0.01wt%-0.07wt%) and boric acid (0.1wt%-0.3 wt%) mixed solution at 85-90℃ for secondary formation for 7-10min, the formation voltage is 290-300V, then placed in a mixture of citric acid (0.02wt%-0.04wt%), ammonium citrate (0.03wt%-0.08wt%) and boric acid (0.4wt%-1 wt%) at 85-90℃ for tertiary formation for 7-10min, the formation voltage is 440-450V, then placed in a mixture of citric acid (0.01wt%-0.03wt%), ammonium citrate (0.04wt%-0.06wt%), boric acid (0.4wt%-1wt%), azelaic acid (0.003wt%-0.005wt%) at 85-90℃ for quaternary formation for 15-20min, the formation voltage is 440-450V, and ... The voltage is 550-560V; then it is placed in ammonia water (70wt%-80wt%) and boiled at 60-80℃ for 5-10min, and then placed in a mixture of citric acid (0.01wt%-0.03wt%), ammonium citrate (0.04wt%-0.06wt%), boric acid (0.4wt%-1wt%), and azelaic acid (0.003wt%-0.005wt%) at 85-90℃ for the next step of chemical reaction for 15-20min. min, the formation voltage is 550-560V, then placed in ammonia water (70wt%-80wt%) at 60-80℃ for 5-10min, washed with water, heat treated at 450-500℃ for 5-7min, and then placed in a mixture of citric acid (0.002wt%-0.01wt%), ammonium citrate (0.002wt%-0.01wt%) and boric acid (0.1wt%-0.5wt%) for 85-9 After the secondary formation at 0℃ for 12-15min, the formation voltage is 550-560V, then it is placed in phosphoric acid (7wt%-10wt%) and boiled at 85-90℃ for 5-7min, washed with water, heat treated at 450-500℃ for 5-7min, and then placed in citric acid (0.002wt%-0.01wt%), ammonium citrate (0.002wt%-0.01wt%) and boric acid (0.1wt%-0.5wt%) mixed solution at 85-90℃ for 12-15min, the voltage is 550-560V, then placed in diammonium phosphate (7wt%-10wt%) and boiled at 85-90℃ for 5-7min, and finally dried in an oven at 100-150℃.

[0024] Beneficial effects of the present invention: Compared with the traditional pore-forming process, the high-thickness aluminum foil anode foil composite pulse waveform pore-forming technology of the present invention can significantly improve the electrostatic capacitance and mechanical properties of the high-thickness corrosion foil finally obtained.

[0025] The high-thickness aluminum foil anode foil composite pulse waveform pore-forming technology of the present invention uses low-frequency pulse superposition in the initial stage of pore-forming during the pulse pore-forming process, and uses high-frequency pulse superposition in the middle and late stages of tunnel hole growth, so that the density and uniformity of the holes on the surface of the aluminum foil are significantly improved, thereby further improving the electrostatic capacitance and mechanical strength of the corrosion foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art description.

[0027] Figure 1 This is a microscopic characterization diagram of the residual core layer of the sample obtained in Example 2 of the present invention;

[0028] Figure 2 This is a microscopic characterization image of the surface layer of the sample obtained in Example 2 of the present invention;

[0029] Figure 3 This is a microscopic characterization diagram of the residual core layer of the sample obtained in Comparative Example 4 of the present invention;

[0030] Figure 4 This is a microscopic characterization image of the surface layer of the sample obtained in Comparative Example 4 of the present invention;

[0031] Figure 5 This is a schematic diagram of the composite pulse superposition waveform when the pulse is emitted in Example 2 of the present invention;

[0032] Figure 6 This is a local enlarged view of the composite pulse superposition waveform when the pulse is emitted in Example 2 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0034] The thickness of the thick foil used in the embodiment of the present invention and the comparative example is 145 μm; the chemical formation process used in the embodiment of the present invention and the comparative example is as follows: the obtained aluminum foil is boiled in 93°C pure water for 10 minutes, then placed in a mixture of adipic acid (0.1wt%), ammonium adipate (0.2wt%), boric acid (0.1wt%) and maleic acid (0.05wt%) for primary formation at 93°C for 8 minutes, the formation voltage is 165V, then placed in a mixture of citric acid (0.05wt%), ammonium citrate (0.04wt%) and boric acid (0.2wt%) The mixture was subjected to secondary reaction at 87°C for 8 min at a voltage of 295 V, and then placed in a mixture of citric acid (0.03 wt%), ammonium citrate (0.05 wt%) and boric acid (0.7 wt%) for tertiary reaction at 87°C for 7 min at a voltage of 447 V, and then placed in a mixture of citric acid (0.02 wt%), ammonium citrate (0.05 wt%), boric acid (0.7 wt%) and azelaic acid (0.004 wt%) for quaternary reaction at 87°C for 17 min at a voltage of 555 V; then placed in ammonia (75 w t%), boiled at 60-80℃ for 8min, then placed in a mixture of citric acid (0.02wt%), ammonium citrate (0.05wt%), boric acid (0.5wt%), and azelaic acid (0.004wt%) for post-chemical reaction at 87℃ for 17min, with a chemical reaction voltage of 557V, then boiled in ammonia water (75wt%) at 70℃ for 7min, washed with water, heat treated at 480℃ for 6min, then placed in a mixture of citric acid (0.008wt%), ammonium citrate (0.007wt%) and boric acid (0.4wt%) The mixture was subjected to secondary chemical reaction at 87°C for 13 min at a voltage of 555 V, then boiled in phosphoric acid (8wt%) at 88°C for 6 min, washed with water, heat treated at 480°C for 6 min, then subjected to tertiary chemical reaction at 88°C for 14 min in a mixture of citric acid (0.006wt%), ammonium citrate (0.008wt%) and boric acid (0.3wt%) at a voltage of 555 V, then boiled in diammonium phosphate (8wt%) at 88°C for 6 min, and finally dried in an oven at 130°C.

[0035] The remaining parameters of the chemical formation process are all OK and will not be elaborated in detail in the present invention.

[0036] Example 1: A high-thickness aluminum foil anode foil composite pulse waveform hole-making technology, the specific process is as follows:

[0037] (1) Place a 145 μm thick foil in a 65°C, 1.5 mol / L phosphoric acid solution, take it out after 120 seconds, and wash it thoroughly with pure water;

[0038] (2) The aluminum foil obtained in (1) was placed in a mixed bath of 0.5 mol / L hydrochloric acid, 3.2 mol / L sulfuric acid and 0.01 mol / L phosphoric acid, and pulsed pores were generated at 60°C. First, the aluminum foil was pulsed at 1.7 A / cm 2 Duration 0.5s, superimposed pulse, frequency 500Hz, duty cycle 30%, superimposed size ±0.03A / cm 2 ; then at 1.2 A / cm 2 1.5s duration, superimposed pulse, frequency 700Hz, duty cycle 45%, superimposed size ±0.03A / cm 2 ; then 0.5 A / cm 2 Lasts for 1.5s, superimposed pulse, frequency 700Hz, duty cycle 45%, superimposed size ±0.03A / cm 2 ; then at 0.3 A / cm 2 2s duration, superimposed pulse, frequency 800Hz, duty cycle 45%, superimposed size ±0.02A / cm 2 ; Finally, 0.15A / cm 2 Lasts for 10s, superimposed pulse, frequency 1000Hz, duty cycle 45%, superimposed size ±0.01A / cm 2 After repeating the above pore-forming steps 3 times, 2 Duration 0.5s, superimposed pulse, frequency 500Hz, duty cycle 30%, superimposed size ±0.03A / cm 2 ;

[0039] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.1 mol / L nitric acid, 0.05 mol / L phosphoric acid, and 0.02 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 60 °C and a constant current density of 0.12 A / cm 2 , duration is 13min;

[0040] (4) The aluminum foil obtained in (3) was placed in a 0.03 mol / L dilute hydrochloric acid solution, washed at 60°C for 1 min, then placed in a 0.1 mol / L dilute nitric acid solution, washed at 65°C for 1 min, rinsed with pure water for 8 min, and dried at 180°C;

[0041] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0042] Example 2: A high-thickness aluminum foil anode foil composite pulse waveform hole-making technology, the specific process is as follows:

[0043] (1) Place a 145 μm thick foil in a 68°C, 2.5 mol / L phosphoric acid solution, take it out after 60 seconds, and wash it thoroughly with pure water;

[0044] (2) Place the aluminum foil obtained in (1) in a mixed bath of 0.8 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.03 mol / L phosphoric acid and perform pulse pore generation at 65°C. 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 34%, superimposed size is ±0.04A / cm 2 ; then at 1.4 A / cm 2 Lasts for 2.5s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; then at 0.8 A / cm 2 Lasts for 2s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; then at 0.4 A / cm 2 4s duration, superimposed pulse, frequency 850Hz, duty cycle 48%, superimposed size ±0.03A / cm 2 ; Finally, 0.25 A / cm 2 Lasts for 13s, superimposed pulse, frequency 1300Hz, duty cycle 48%, superimposed size ±0.015A / cm 2 After repeating the above pore-forming steps 4 times, the 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 33%, superimposed size is ±0.04A / cm 2 ;

[0045] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.3 mol / L nitric acid, 0.1 mol / L phosphoric acid and 0.05 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 70 °C and a constant current density of 10 A / cm 2 , duration is 15min;

[0046] (4) The aluminum foil obtained in (3) was placed in a 0.07 mol / L dilute hydrochloric acid solution, washed at 63°C for 2 min, then placed in a 0.2 mol / L dilute nitric acid solution, washed at 68°C for 2 min, rinsed with pure water for 12 min, and dried at 220°C;

[0047] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0048] Embodiment 3: A high-thickness aluminum foil anode foil composite pulse waveform hole-making technology, the specific process is as follows:

[0049] (1) Place a 145 μm thick plain foil in a 70°C, 3 mol / L phosphoric acid solution, take it out after 30 seconds, and wash it thoroughly with pure water;

[0050] (2) The aluminum foil obtained in (1) was placed in a mixed bath of 1 mol / L hydrochloric acid, 3.8 mol / L sulfuric acid and 0.05 mol / L phosphoric acid, and pulsed pores were generated at 73°C. First, the aluminum foil was heated at 1.9 A / cm 2 Lasts for 2s, superimposed pulse, frequency is 700Hz, duty cycle is 37%, superimposed size is ±0.05A / cm 2 ; then at 1.7 A / cm 2 3s duration, superimposed pulse, frequency 800Hz, duty cycle 50%, superimposed size ±0.05A / cm 2 ; then at 1.2 A / cm 2 Lasts for 3s, superimposed pulse, frequency 800Hz, duty cycle 50%, superimposed size ±0.05A / cm 2 ; then at 0.5 A / cm 2 5s duration, superimposed pulse, frequency 900Hz, duty cycle 50%, superimposed size ±0.03A / cm 2 ; Finally, 0.3 A / cm 2 15s duration, superimposed pulse, frequency 1500Hz, duty cycle 50%, superimposed size ±0.015A / cm 2 After repeating the above pore-forming steps 5 times, 2 Lasts for 2s, superimposed pulse, frequency is 700Hz, duty cycle is 37%, superimposed size is ±0.05A / cm 2 ;

[0051] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.5 mol / L nitric acid, 0.1 mol / L phosphoric acid and 0.08 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 80 °C and a constant current density of 17 A / cm 2 , duration is 16min;

[0052] (4) The aluminum foil obtained in (3) was placed in a 0.1 mol / L dilute hydrochloric acid solution and washed at 65°C for 3 min, then placed in a 0.2 mol / L dilute nitric acid solution and washed at 70°C for 3 min, then rinsed with pure water for 15 min, and dried at 270°C;

[0053] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0054] Comparative Example 1: A high-thickness aluminum foil anode foil pulse pore-forming technology, which differs from Example 2 in that the last low-frequency treatment is not performed, and the specific process is as follows:

[0055] (1) Place a 145 μm thick foil in a 68°C, 2.5 mol / L phosphoric acid solution, take it out after 60 seconds, and wash it thoroughly with pure water;

[0056] (2) Place the aluminum foil obtained in (1) in a mixed bath of 0.8 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.03 mol / L phosphoric acid and perform pulse pore generation at 65°C. 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 34%, superimposed size is ±0.04A / cm 2 ; then at 1.4 A / cm 2 Lasts for 2.5s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; then at 0.8 A / cm 2 Lasts for 2s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; then at 0.4 A / cm 2 4s duration, superimposed pulse, frequency 850Hz, duty cycle 48%, superimposed size ±0.03A / cm 2 ; Finally, 0.25 A / cm 2 Lasts for 13s, superimposed pulse, frequency 1300Hz, duty cycle 48%, superimposed size ±0.015A / cm 2 , the above-mentioned hole-making steps are repeated 4 times;

[0057] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.3 mol / L nitric acid, 0.1 mol / L phosphoric acid and 0.05 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 70 °C and a constant current density of 10 A / cm 2 , duration is 15min;

[0058] (4) The aluminum foil obtained in (3) was placed in a 0.07 mol / L dilute hydrochloric acid solution, washed at 63°C for 2 min, then placed in a 0.2 mol / L dilute nitric acid solution, washed at 68°C for 2 min, rinsed with pure water for 12 min, and dried at 220°C;

[0059] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0060] Comparative Example 2: A high-thickness aluminum foil anode foil pulse pore-forming technology, which is different from Example 2 in that when performing pulse pore-forming treatment, it is first treated with a high frequency and then with a low frequency. The specific process is as follows:

[0061] (1) Place a 145 μm thick foil in a 68°C, 2.5 mol / L phosphoric acid solution, take it out after 60 seconds, and wash it thoroughly with pure water;

[0062] (2) The aluminum foil obtained in (1) was placed in a mixed bath of 0.8 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.03 mol / L phosphoric acid, and pulsed pores were generated at 65°C. First, the aluminum foil was pulsed at 0.25 A / cm 2 Lasts for 13s, superimposed pulse, frequency 1300Hz, duty cycle 48%, superimposed size ±0.015A / cm 2 ; then at 0.4 A / cm 2 4s duration, superimposed pulse, frequency 850Hz, duty cycle 48%, superimposed size ±0.03A / cm 2 ; then at 0.8 A / cm 2 Lasts for 2s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; then at 1.4 A / cm 2 Lasts for 2.5s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; Finally, 1.8A / cm 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 34%, superimposed size is ±0.04A / cm 2 After repeating the above pore-forming steps 4 times, the 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 33%, superimposed size is ±0.04A / cm 2 ;

[0063] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.3 mol / L nitric acid, 0.1 mol / L phosphoric acid and 0.05 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 70 °C and a constant current density of 10 A / cm 2 , duration is 15min;

[0064] (4) The aluminum foil obtained in (3) was placed in a 0.07 mol / L dilute hydrochloric acid solution, washed at 63°C for 2 min, then placed in a 0.2 mol / L dilute nitric acid solution, washed at 68°C for 2 min, rinsed with pure water for 12 min, and dried at 220°C;

[0065] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0066] Comparative Example 3: A high-thickness aluminum foil anode foil pulse pore-forming technology, which differs from Example 2 in that the mixed treatment is performed, and the specific process is as follows:

[0067] (1) Place a 145 μm thick foil in a 68°C, 2.5 mol / L phosphoric acid solution, take it out after 60 seconds, and wash it thoroughly with pure water;

[0068] (2) Place the aluminum foil obtained in (1) in a mixed bath of 0.8 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.03 mol / L phosphoric acid and perform pulse pore generation at 65°C. First, pulse pore generation at 0.4 A / cm 2 4s duration, superimposed pulse, frequency 850Hz, duty cycle 48%, superimposed size ±0.03A / cm 2 ; then at 0.8 A / cm 2 Lasts for 2s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; then at 1.8A / cm 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 34%, superimposed size is ±0.04A / cm 2 ; then at 1.4 A / cm 2 Lasts for 2.5s, superimposed pulse, frequency 750Hz, duty cycle 48%, superimposed size ±0.04A / cm 2 ; Finally, 0.25 A / cm 2 Lasts for 13s, superimposed pulse, frequency 1300Hz, duty cycle 48%, superimposed size ±0.015A / cm 2 After repeating the above pore-forming steps 4 times, the 2 Lasts for 1.5s, superimposed pulse, frequency is 600Hz, duty cycle is 33%, superimposed size is ±0.04A / cm 2 ;

[0069] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.3 mol / L nitric acid, 0.1 mol / L phosphoric acid and 0.05 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 70 °C and a constant current density of 10 A / cm 2 , duration is 15min;

[0070] (4) The aluminum foil obtained in (3) was placed in a 0.07 mol / L dilute hydrochloric acid solution, washed at 63°C for 2 min, then placed in a 0.2 mol / L dilute nitric acid solution, washed at 68°C for 2 min, rinsed with pure water for 12 min, and dried at 220°C;

[0071] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0072] Comparative Example 4: A high-thickness aluminum foil anode foil pulse pore-forming technology, the specific process is as follows:

[0073] (1) Place a 145 μm thick foil in a 68°C, 2.5 mol / L phosphoric acid solution, take it out after 60 seconds, and wash it thoroughly with pure water;

[0074] (2) Place the aluminum foil obtained in (1) in a mixed bath of 0.8 mol / L hydrochloric acid, 3.5 mol / L sulfuric acid and 0.03 mol / L phosphoric acid and perform pulse pore generation at 65°C. 2 Continue for 1.5 s, then at 1.4 A / cm 2 Continue for 2.5s, then at 0.8 A / cm 2 Continue for 2 seconds, then at 0.4 A / cm 2 Continue for 4 seconds, and finally at 0.25 A / cm 2 Continue for 13 seconds, and repeat the above pore-forming steps 4 times;

[0075] (3) The aluminum foil obtained in (2) was placed in a mixed bath of 1.3 mol / L nitric acid, 0.1 mol / L phosphoric acid and 0.05 g / L sodium polystyrene sulfonate for pore expansion at a temperature of 70 °C and a constant current density of 10 A / cm 2 , duration is 15min;

[0076] (4) The aluminum foil obtained in (3) was placed in a 0.07 mol / L dilute hydrochloric acid solution, washed at 63°C for 2 min, then placed in a 0.2 mol / L dilute nitric acid solution, washed at 68°C for 2 min, rinsed with pure water for 12 min, and dried at 220°C;

[0077] (5) The aluminum foil obtained in (4) is subjected to chemical treatment to obtain a finished etched foil.

[0078] Performance Testing

[0079] Bending strength: The samples obtained in the embodiment and the comparative example were tested using an MIT folding strength tester. The test results are shown in Table 1.

[0080] Electrostatic Capacitance: The samples obtained in the embodiment and the comparative example were tested using an LCR digital automatic bridge. The test results are shown in Table 1.

[0081] Table 1 Performance test results

[0082]

[0083] Data analysis: It can be seen from Examples 1-3 in Table 1 that the etched foil samples finally obtained by the high-thickness aluminum foil anode foil composite pulse waveform pore-forming technology of the present invention have excellent electrostatic capacitance and mechanical properties.

[0084] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the present invention further improves the electrostatic capacitance and mechanical strength of the sample by performing a low-frequency pulse treatment at the end after alternating low-frequency pulses and high-frequency pulses 3-5 times during the pulse pore-generating process. This is most likely because the last low-frequency pulse applied further expands the pores, improves the connectivity and depth of the pores, thereby further improving the specific volume. At the same time, the structure of the pores is further optimized, so that its mechanical properties are also improved.

[0085] It can be seen from Example 2 and Comparative Examples 2 and 3 in Table 1 that the present invention further improves the electrostatic capacitance and mechanical strength of the sample by alternately using low-frequency pulse superposition in the initial stage of pore formation and high-frequency pulse superposition in the middle and late stages of tunnel pore growth during the pulse pore formation process. This is mainly because the use of low-frequency pulses in the initial stage of pore formation can form larger initial pores with uniform pore distribution; the use of high-frequency pulses in the middle and late stages of tunnel pore growth can refine the pores and improve the density and uniformity of the pores. Compared with other pulse treatment methods, this low-frequency-then-high-frequency pulse treatment method can significantly improve the specific volume and mechanical properties of the product.

[0086] It can be seen from Example 2 and Comparative Example 4 in Table 1 that, compared with the traditional pore forming process, the high-thickness etched foil finally obtained by the present invention has obvious improvements in both electrostatic capacitance and mechanical properties.

[0087] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for producing holes with a composite pulse waveform of a high-thickness aluminum foil anode foil, characterized in that: The following steps are involved: S1: Place the plain foil in a phosphoric acid solution and then take it out for washing; S2: subjecting the aluminum foil obtained in S1 to a pore-forming treatment; S3: performing hole expansion treatment on the aluminum foil obtained in S2; S4: washing the aluminum foil obtained in S3 in a dilute hydrochloric acid solution, then washing it in a dilute nitric acid solution, and finally rinsing it with pure water and drying it; S5: performing chemical treatment on the aluminum foil obtained in S4 to obtain a finished corrosion foil; The pore-forming treatment in step S2 is to place the aluminum foil obtained in step S1 in a mixed bath solution of 0.5-1 mol / L hydrochloric acid, 3.2-3.8 mol / L sulfuric acid and 0.01-0.05 mol / L phosphoric acid, and perform a composite pulse pore-forming treatment at a temperature of 60-73° C. The specific process is as follows: First, 1.7-1.9 A / cm 2 Duration 0.5-2s, superimposed pulse, frequency 500-700Hz, duty cycle 30%-37%, superimposed size ±0.03-0.05A / cm 2 ; then at 1.2-1.7 A / cm 2 Duration 1.5-3s, superimposed pulse, frequency 700-800Hz, duty cycle 45%-50%, superimposed size ±0.03-0.05A / cm 2 ; then 0.5-1.2 A / cm 2 Duration 1.5-3s, superimposed pulse, frequency 700-800Hz, duty cycle 45%-50%, superimposed size ±0.03-0.05A / cm 2 ; then at 0.3-0.5 A / cm 2 Lasts 2-5s, superimposed pulse, frequency 800-900Hz, duty cycle 45%-50%, superimposed size ±0.02-0.03A / cm 2 ; Finally, 0.15-0.3 A / cm 2 Duration 10-15s, superimposed pulse, frequency 1000-1500Hz, duty cycle 45%-50%, superimposed size ±0.01-0.015A / cm 2 After repeating the above pore-forming steps 3-5 times, 2 Duration 0.5-2s, superimposed pulse, frequency 500-700Hz, duty cycle 30%-37%, superimposed size ±0.03-0.05A / cm 2 .

2. The high-thickness aluminum foil anode foil composite pulse waveform hole-making method according to claim 1, characterized in that: In step S1, the concentration of the phosphoric acid solution is 1.5-3 mol / L, the temperature is 65-70° C., and the time is 30-120 s.

3. The method for making holes in a high-thickness aluminum foil anode foil with a composite pulse waveform according to claim 1, characterized in that: The pore expansion treatment in step S3 is to place the aluminum foil obtained in step S2 in a mixed bath solution of 1.1-1.5 mol / L nitric acid, 0.05-0.1 mol / L phosphoric acid and 0.02-0.08 g / L sodium polystyrene sulfonate for pore expansion treatment.

4. The high-thickness aluminum foil anode foil composite pulse waveform hole-making method according to claim 3, characterized in that: The temperature of the hole expansion treatment is 60-80°C and the constant current density is 0.12-17 A / cm 2 , duration is 13-16 minutes.

5. The method for producing holes with composite pulse waveform of high thickness aluminum foil anode foil according to claim 1, characterized in that: In step S4, the concentration of the dilute hydrochloric acid solution is 0.03-0.1 mol / L, and the concentration of the dilute nitric acid solution is 0.1-0.2 mol / L.

6. The method for producing holes with composite pulse waveform of high thickness aluminum foil anode foil according to claim 1, characterized in that: The pure water rinsing time in step S4 is 8-15 minutes.

7. The method for making holes in a high-thickness aluminum foil anode foil with a composite pulse waveform according to claim 1, characterized in that: The drying temperature in step S4 is 180-270°C.

Citation Information

Patent Citations

  • Method for preparing mid-high voltage corrosion foil by using pulse DC superposed current

    CN104505260A

  • Low-pressure corrosion foil as well as preparation method and application thereof

    CN118957725A